Revealing the Social Values through Signs in the Novel Paper Towns by John Green - Ashari, Mutmainah; Rosmiati, Rosmiati; Janah, Ulum (Prologue: Journal on Language and Literature, 2020)
This research analyzes about the signs represented social values in the novel Paper Towns. There are two objectives that become the purpose of this study: 1) to explain the types of social values in the novel Paper Towns by John Green and 2) to analyze the signs which reveal the social values in the novel Paper Towns by John Green. The theory used in this research is the Semiotics approach by using theory of Charles Sanders Peirce, there are Qualisign, Sinsign and Legisign. The methodology used in this study is descriptive qualitative research to explain the data, because the data are analyzed in the form of words and sentences. The data are taken from the sentences and the conversation in the text in the novel Paper Towns by John Green. The result of the research, the researcher found 4 types of social values. There are stimulation, hedonism, security, and conformity. The researcher found signs of words in the novel and analyze the signs using Charles Sanders Peirce's theory and then the researcher revealed social values through signs based on the types of social values by Schawartz.